Adolescent physical activity during school days: a comparative study before and after COVID-19 pandemic restrictions - Frömel, Karel; Welk, Gregory; Groffik, Dorota; Jakubec, Lukáš; Dygrýn, Jan; Mitáš, Josef (Frontiers in Public Health, 2025)
BackgroundPhysical activity (PA) during the school day is crucial for the health and well-being of adolescents. This study examines the impact of the COVID-19 pandemic on youth PA patterns to better understand these changes and to provide guidelines for school programming.MethodsDifferences in PA within specific segments of the school day were examined before and after the pandemic using the Youth Activity Profile questionnaire. Participants included 956 boys and 1,317 girls from 21 high schools. The study involved 12 Czech and 9 Polish high schools before the pandemic and 9 Czech and 8 Polish high schools after the pandemic.ResultsBoth Czech and Polish boys and girls exhibited significantly less transportation PA to and from school and reduced PA during the school day after the pandemic compared to before. Additionally, Czech and Polish boys were significantly less physically active during school breaks, and Czech boys and girls had notably less PA during physical education lessons. The pandemic disrupted the habit of regular PA on school days, particularly evident in the decline of PA to and from school.ConclusionThe study confirms a significant difference in PA of Czech and Polish adolescents in various segments of the school day after students return to school following pandemic restrictions. Promoting achievement of the recommendations in the segments of the school day and in comprehensive school PA programs should be an important part of school health and education policy and public health promotion for adolescents.